The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1021/om030089s
|View full text |Cite
|
Sign up to set email alerts
|

Organocobaloximes with Mixed Dioxime Equatorial Ligands:  A Convenient One-Pot Synthesis. X-ray Structures and Cis−Trans Influence Studies

Abstract: A simple and general route to the synthesis of organocobaloxime with mixed dioxime ligands, RCo(L)(dpgH)Py [L ) dmgH and chgH] (R ) Me-Dec), has been described. The crystal structure of four complexes, ClCo(L)(dpgH)Py and MeCo(L)(dpgH)Py [L ) dmgH and chgH], is reported. The structural study reveals that both the nonclassical C-H‚‚‚O as well as the classical O-H‚‚‚O intermolecular hydrogen bonding is present and leads to the formation of one-dimensional dimeric or polymeric structures. 1 H and 13 C NMR coordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 57 publications
3
20
0
Order By: Relevance
“…Recently, inter and intra-molecular weak interactions of monocobaloximes have been discussed by Gupta et al [29,30]. In our cases, it is of interest to note that prismatic crystal 2 can be stored in air for months, however, claviform crystals 1 and 3 would effloresce within a few minutes once exposure to air.…”
Section: Packing Structurementioning
confidence: 66%
“…Recently, inter and intra-molecular weak interactions of monocobaloximes have been discussed by Gupta et al [29,30]. In our cases, it is of interest to note that prismatic crystal 2 can be stored in air for months, however, claviform crystals 1 and 3 would effloresce within a few minutes once exposure to air.…”
Section: Packing Structurementioning
confidence: 66%
“…The proposed intramolecular H-bonding interactions are reminiscent of those reported for pyridyl pyrazolate Os complexes as well as cobaloxime complexes. [10] It is believed that this unusual H-bonding pattern, to a certain extent, provides a strong driving force to stabilize the observed trans-geometry. In contrast to our discovery, the X-ray structural analyses of related Pt II complexes such as Pt(thppy) 2 , where thppy is 2-(2¢-thienyl) pyridine, revealed that ligated thiophene and pyridine fragments are oriented exclusively in a cis-configuration, despite the large distortion and deformation of square planar geometry that occurred at the junction of the ligands.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…Of particular interest are the relatively weak nonbonding contacts (N3A -H1 ∼ 2.50 Å ) observed between the ortho -hydrogen atom of the pyridyl moiety and the N atom of the nearby pyrazolate fragment. It is speculated that this hydrogen bonding, to a certain extent, is akin to that observed in the cobaloxime complexes [40] . As indicated in Table 5.3 , the UV/Vis spectra of these osmium complexes showed similar patterns, with three notable absorption maxima.…”
Section: Red -Emitting Materialsmentioning
confidence: 85%